Ε-Viniferin, a promising natural oligostilbene, ameliorates hyperglycemia and hyperlipidemia by activating AMPK in vivo. Issue 11 (3rd November 2020) - Liu, Ruijuan; Zhang, Yang; Yao, Xin; Wu, Qi; Wei, Minggang; Yan, Zhaowei
Abstract : This study aimed to investigate the beneficial effects of ε-Viniferin on hyperglycemia and hyperlipidemia, and reveal the underlying mechanism. Abstract : ε-Viniferin (VNF), a naturally occurring oligostilbene (a resveratrol dimer), is mainly found in grapes and red wines. However, unlike resveratrol, the biological activity of VNF has not been widely studied. This study was conducted to investigate the beneficial effects of VNF on hyperglycemia and hyperlipidemia and further to reveal the underlying mechanism. The ameliorative effects of VNF in high-fat-diet and streptozotocin-induced type 2 diabetic rats were assessed physiologically, biochemically and histologically after oral administration of VNF (30 mg kg −1 and 60 mg kg −1 ) for 8 weeks. Western blotting and immunohistochemistry experiments were performed to determine the effects of VNF on the AMPK phosphorylation levels in the livers of diabetic rats. Molecular docking and molecular dynamics simulation were further performed to study the molecular-level interaction between VNF and AMPK. Meanwhile, the protective effects of VNF on the liver and kidney were also evaluated. The results showed that the VNF treatment caused a significant decrease in the concentrations of fasting blood glucose (FBG), total cholesterol (TC), triglyceride (TG), and low density lipoprotein-cholesterol (LDL-C), and improved the glucose tolerance of diabetic rats. In addition, the liver and kidney damage indices such as alanine aminotransferase (ALT), aspartate aminotransaminase (AST), creatinine (CR), and blood urea nitrogen (BUN) were also lowered and improved. Moreover, VNF could increase the AMPK activation and attenuate histopathological changes in the liver of diabetic rats. The molecular docking and molecular dynamics simulation results revealed for the first time that VNF bound to the hinge region between the α- and β-units of AMPK and interacted with the active site of AMPK. In conclusion, VNF can effectively improve hyperglycemia and hyperlipidemia and exhibit protective effects on the liver and kidney functions. The underlying mechanism of VNF in hyperglycemia and hyperlipidemia may be related to the activation of AMPK in vivo . Our findings indicate that VNF is a potentially useful natural agent for the treatment of metabolic diseases, especially type 2 diabetes and hyperlipidemia.